2012
DOI: 10.1016/j.bpj.2011.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Depth of α-Synuclein in a Bilayer Determined by Fluorescence, Neutron Reflectometry, and Computation

Abstract: α-Synuclein (α-syn) membrane interactions are implicated in the pathogenesis of Parkinson's disease. Fluorescence and neutron reflectometry (NR) measurements reveal that α-syn penetrates ∼9-14 Å into the outer leaflet of the bilayer, with a substantial portion of the membrane-bound polypeptide extending into the aqueous solvent. For the first time, to our knowledge, we used NR to obtain direct quantitative evidence of α-syn-induced membrane thinning. To examine the effect of specific residues on membrane penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
139
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(160 citation statements)
references
References 89 publications
19
139
2
Order By: Relevance
“…A minor thinning of the bilayer to free space for the protein in the headgroup layer was needed in the modeling, which is also consistent with the previous NR study for another lipid composition and pH. 28 However, the thinning does not free enough space for the protein to be located between the outer phospholipid headgroups. A perturbed acyl chain packing with increased water content in the acyl chain layer is needed in addition to the thinning of the bilayer to observe a good fit while preserving stoichiometric relations.…”
Section: 62supporting
confidence: 84%
“…A minor thinning of the bilayer to free space for the protein in the headgroup layer was needed in the modeling, which is also consistent with the previous NR study for another lipid composition and pH. 28 However, the thinning does not free enough space for the protein to be located between the outer phospholipid headgroups. A perturbed acyl chain packing with increased water content in the acyl chain layer is needed in addition to the thinning of the bilayer to observe a good fit while preserving stoichiometric relations.…”
Section: 62supporting
confidence: 84%
“…5C). The observed changes cannot simply be due to crowding at the membrane surface; ␣-syn in the absence of GCase has been measured at comparable membrane coverage, and no changes have been observed resembling those seen for the complex (34). Unfortunately, we are near the limit of detection by NR, so lowering protein concentrations of ␣-syn and GCase below 300 nM is not feasible at this time; therefore, it is uncertain to what extent steric contacts might be perturbing the NR results.…”
Section: Effect Of ␣-Synuclein On Gcase Membrane Binding Probed Bymentioning
confidence: 89%
“…In general, the amino acid sequences of these peripheral proteins are characterized by patterns of hydrophobic and polar residues such that the proteins fold into amphipathic α-helices upon binding to hydrophobic patches exposed at the membrane interface (16,17). In particular, molecular dynamics simulations and neutron reflectometry studies of deposited bilayers have shown that the amphipathic helix in α-synuclein is primarily located in the vicinity of the lipid phosphate groups and the glycerol backbone (16,(23)(24)(25).…”
mentioning
confidence: 99%